Finite-Time Tracking Control of Rigid Spacecraft Under Actuator Saturations and Faults - Lu, Kunfeng; Xia, Yuanqing; Yu, Chunmei; Liu, Hailiang (IEEE transactions on automation science and engineering, 2016)
In this paper, an adaptive fast terminal sliding mode control control law (AFTSMCL) is presented to resolve attitude tracking control problem for rigid spacecraft, which can provide finite-time convergence, strong robustness, and fault-tolerant control. Rigorous proof is achieved first. Simulation results are presented to illustrate the effectiveness of presented control law.